Pelayanan Pendidikan di Daerah Terpencil: Problematika Pendidikan di Indonesia (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to determine educational services in remote areas by referring to educational problems in Indonesia and the factors that cause them. The research method we use is a qualitative literature study method. With the data collection system in this research, it comes from books, journals and analyzed articles that are relevant to the problem being studied. The results of this research show that education services in remote areas are still inadequate and there are still many problems that need to be overcome, such as lack of access to education, facilities and infrastructure and a lack of professional teachers